Manipulator design for a mobile robotic platform - Nyi, Myo Aung (2010)
The Tech-X challenge is a competition organized by Defense Science & Technology Agency (DSTA), Singapore’s National authority for defense science and technology. The Tech-X robots are required to carry out the autonomous navigation and target identification and engagement in the competition. To identify and engage the target, the Tech-X robot needs to press an intended elevator control button and precisely need to touch the designated button. Moreover the manipulator must be able to pick up or move the 2 kg payload from the ground or any location which must be within the robot’s reachable range. In order to execute and complete these tasks, the Tech-X robot needs to integrate with the robot manipulator. Therefore the manipulator becomes one of the most important features in the Tech-X robot. The author was assigned to design and develop the new manipulator complying with the competition requirements for the NTU School of Mechanical and Aerospace Engineering team. The literature review was done on different types of robot arm and their configuration before going for the conceptual designs section. Numerous possible conceptual configurations were generated and one of the best configuration s was selected by evaluating method. A 6-degrees- of- freedom series robot arm which has five revolute joints and one prismatic joint was selected. The robot arm model was designed in the Solidworks software. Since the fabrication process has not started yet, the necessary simulation analysis was performed to analyze to predict the performance of the robot manipulator. Moreover, using forward kinematic logic, a work envelope of manipulator was created to study the maximum and minimum range that manipulator can reach and flexibility of the robot arm.